La construction identitaire et le principe d’altérité. La Pologne comme l’Autre dans le discours de la presse écrite quotidienne en France - Biardzka , Elżbieta; Paskart , Patrycja (Studia Romanica Posnaniensia, 2024)
This study aims to show how the principle of otherness emerges in the discourse of the national written press in France. We consider that in the media, the Other is Poland, whose social meaning, stored in the collective memory, embraces the extremely negative traits of difference and threat. The judgment of otherness relates to four components of this meaning. Firstly, Poland is perceived as an object whose location is indefinite and undecided. Secondly, it is strange due to its excessive, aggressive and dangerous Catholicism. Thirdly, it harms France and the common European project. Finally, it constitutes an economic threat.